Efectividad de la terapia de aceptación y compromiso para pacientes con trastorno obsesivo compulsivo - Rodriguez Mariategui Jahnsen, Karen Ariana (2022)
Obsessive-compulsive disorder (OCD) has been recognized as one of the most common and debilitating disorders, which is why different types of interventions have been used to try to treat it. Acceptance and commitment therapy (ACT) emerges as a novel proposal, given it has a different approach which has obtained good results in other clinical diagnoses. The objective of the present study is to identify the efficacy of ACT in obsessive-compulsive disorder (OCD). For this, a systematic search was carried out following the PRISMA guidelines (Page, et al., 2020), using Scopus, Web of Science and Scielo electronic databases. Ten articles were selected which met the defined inclusion and exclusion criteria. The results of these studies unanimously show that ACT is effective for the treatment of OCD as it has a significant impact in reducing symptoms. In addition, the reduction of symptoms was maintained, and in some cases it continued to decrease after a 3 month follow up. Some studies mentioned that ACT is effective in treating OCD, mainly when combined with pharmacological treatment.